Kanak-kanak dan remaja menggunakan gajet - Abdul Khaiyom, Jamilah Hanum (Green Crescent Malaysia, 2019)
The book chapter discuss about the children and adolescence using gadget and its consequences if not being managed properly i.e., addiction.